An ontology and context based client model for dart information grid. (3rd January 2006) - Wu, Z.; Mao, Y.; Chen, H.; Xu, Z.
The WWW is growing at an astounding rate and various autonomous organisations have disseminated heterogeneous information resources in an 'out of order' state, across the web. It is expected to have the ability of integrating and sharing largescale information resources in dynamic virtual organisations. Integrating semantics with context theory, we propose an 'ontology based context role' model (OCR Model) for constructing intelligent clients to information grids. We implement the OCR Model as a semantic browser, which is a novel client for DartGrid and aims at providing end users with an intelligent graphical interface for accessing information effectively in the Grid environment. The semantic browser has been applied in the field of Traditional Chinese Medicine (TCM) to resolve some practical problems.